2010
DOI: 10.1016/j.metabol.2009.09.023
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the metabolic and physiologic response to chromium supplementation in subjects with type 2 diabetes mellitus

Abstract: OBJECTIVE To provide a comprehensive evaluation of chromium (Cr) supplementation on metabolic parameters in a cohort of Type 2 DM subjects representing a wide phenotype range and to evaluate changes in “responders” and “non-responders”. DESIGN After pre-intervention testing to assess glycemia, insulin sensitivity (assessed by euglycemic clamps), Cr status, body composition, subjects were randomized in a double-blind fashion to placebo or 1,000 μg Cr. A sub-study was performed to evaluate 24 hour energy balan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
61
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(67 citation statements)
references
References 25 publications
5
61
1
Order By: Relevance
“…They included both type 1 and type 2 DM, gestational DM, and even steroid-induced diabetes. In the present meta-analysis, four studies showed that Cr has no significant effect on HbA1c (13,15,16,19). In two other studies (17,18), a 0.7% and 1.16% reductions in HbA1c was reported for Cr, respectively.…”
Section: Discussionmentioning
confidence: 46%
See 1 more Smart Citation
“…They included both type 1 and type 2 DM, gestational DM, and even steroid-induced diabetes. In the present meta-analysis, four studies showed that Cr has no significant effect on HbA1c (13,15,16,19). In two other studies (17,18), a 0.7% and 1.16% reductions in HbA1c was reported for Cr, respectively.…”
Section: Discussionmentioning
confidence: 46%
“…The summary for effect size of weighted mean differences of BMI change "∆BMI" in diabetic patients in Cr supplement therapy for six included trials comparing to Pl retrieved from five studies (13,(15)(16)(17)19) was -0.07 with 95% CI= -0.37 to 0.23 (P= 0.66, Figure 9-a). The Cochrane Q test for heterogeneity indicated that the studies are not heterogeneous (P= 0.73) and could be combined, thus the fixed effects for individual and summary of effect size for weighted mean differences was applied.…”
Section: Effect Of Cr On Bmi In Diabetic Patientsmentioning
confidence: 99%
“…Abbreviations: Cr, chromium; IGT, impaired glucose tolerance; RCTs, randomized controlled trials. 22 Cefalu et al (2010) 23 Chen et al (2014) 24 Crawford et al (1999) 25 Evans (1989) 26 Ghosh et al (2002) 27 Gunton et al (2005) 28 Grant and McMullen. (1982) 29 Grant et al (1997) 30 Hermann et al (1998) 31 Hermann et al (1994) 32 Jain et al (2012) 40 Lee and Reasner (1994) 41 Li et al (1992) 42 Li (1994) 43 45 Martinez et al (1985) 46 Mossop (1983) 47 Offenbacher and Pi-Sunyer (1980) 48 Offenbacher et al (1985) 49 Pasman et al (1997) 50 Pei et al (2006) 51 Rabinovitz et al (1983) 52 Rabinovitz et al (2004) 53 Racek et al (2006) 54 Riales et al (1981) 55 Singer and Geohas (2006) 56 Sharma et al (2011) 57 Sherman et al (1968) 58 Thomas and Gropper (1996) 59 Urberg and Zemel (1987) …”
Section: Studies Measuring Hba1cmentioning
confidence: 99%
“…In relation to the lack of effect of supplementation, CrPic can play an antioxidant effect when there is an oxidative disruption, because CrPic supplementation could preserve the antioxidant status when there are a depletion of antioxidant enzymes and an increase in oxidative stress [51][52][53]. In the present study, positive action of CrPic was not observed, likely because there was no depletion of antioxidant enzymes or increased oxidative stress in our sample.…”
Section: Discussionmentioning
confidence: 61%